Reducing spurious flow in simulations of electrokinetic phenomena - Rempfer, Georg; Davies, Gary B.; Holm, Christian; de Graaf, Joost (The Journal of chemical physics, 2016)
Electrokinetic transport phenomena can strongly influence the behaviour of macromolecules and colloidal particles in solution, with applications in, e.g., DNA translocation through nanopores, electro-osmotic flow in nanocapillaries, and electrophoresis of charged macromolecules. Numerical simulations are an important tool to investigate these electrokinetic phenomena, but are often plagued by spurious fluxes and spurious flows that can easily exceed physical fluxes and flows. Here, we present a method that reduces one of these spurious currents, spurious flow, by several orders of magnitude. We demonstrate the effectiveness and generality of our method for both the electrokinetic lattice-Boltzmann and finite-element-method based algorithms by simulating a charged sphere in an electrolyte solution and flow through a nanopore. We also show that previous attempts to suppress these spurious currents introduce other sources of error.